Verapamil for treatment of Fetal Supraventricular Tachycardia - Singh, Amit Kumar; Thakur, Murari; Singh, Ruby; Mandal, Jitendra (Nepalese Heart Journal, 2023)
Fetal arrythmia is reported to affect 1-2% of pregnancies. Besides digoxin not many drugs have been tried in treating such cases. After confirming 1:1 conduction between atrium and ventricle, no structural heart disease of fetus and normal echocardiography and ECG of mother, verapamil was given in the treatment of fetal supraventricular tachycardia. The drug crossed placenta to revert fetus SVT to sinus rhythm without harming mother. The treatment helped fetus against possible complications.